2020
DOI: 10.4103/1673-5374.280320
|View full text |Cite
|
Sign up to set email alerts
|

GFAP expression in the optic nerve and increased H2S generation in the integration centers of the rainbow trout (Oncorhynchus mykiss) brain after unilateral eye injury

Abstract: Hydrogen sulfide (H 2 S) is considered as a protective factor against cardiovascular disorders. However, there are few reports on the effects of H 2 S in the central nervous system during stress or injury. Previous studies on goldfish have shown that astrocytic response occurs in the damaged and contralateral optic nerves. Glial fibrillary acidic protein (GFAP) concentration in the optic nerves of rainbow trout has not been measured previously. This study further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 75 publications
7
5
0
Order By: Relevance
“…The activation of neurons in the cerebellum can lead to the release of glutamate, which, in turn, leads to an increase in intracellular calcium [ 45 , 47 ]. Thus, the wide distribution of type 2 cells in the cerebellum of juvenile O. masou is indicative of mediator–modulator intercellular interactions, which is consistent with previously obtained data on fish [ 12 , 84 ]. The high content of type 2 CBS+ cells also suggests intercellular neuron/glial/microglial interactions associated with the release of H 2 S from intensely labeled glia-like cells and/or microglia [ 86 , 87 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The activation of neurons in the cerebellum can lead to the release of glutamate, which, in turn, leads to an increase in intracellular calcium [ 45 , 47 ]. Thus, the wide distribution of type 2 cells in the cerebellum of juvenile O. masou is indicative of mediator–modulator intercellular interactions, which is consistent with previously obtained data on fish [ 12 , 84 ]. The high content of type 2 CBS+ cells also suggests intercellular neuron/glial/microglial interactions associated with the release of H 2 S from intensely labeled glia-like cells and/or microglia [ 86 , 87 ].…”
Section: Discussionsupporting
confidence: 92%
“…H 2 S is a diffusely spreading gaseous mediator that easily interacts with many signaling molecules, as well as modifies the structure of channel proteins and modulates neuroglia functions [ 47 ]. Thus, the high level of H 2 S production in the cerebellum of juvenile O. masou correlates with high neurogenic activity in the cerebellum and other parts of the brain, which is consistent with the results previously obtained for trout [ 12 ] and other fish species [ 84 ]. Studies on the PCNA localization in the cerebellum of O. masou showed that the patterns of constitutive proliferation were local, small in size, CNNs located in the area of the DMZ, as well as in the molecular layer of all neuroanatomical zones [ 68 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations